PENDEKATAN BERMAIN PERAN UNTUK MENINGKATKAN KETERAMPILAN MENULIS ANGKA DAN NILAI UANG PADA MATA PELAJARAN BAHASA INDONESIA KELAS 4: ROLE PLAY APPROACH TO IMPROVE NUMBERS AND MONEY VALUE WRITING SKILLS IN INDONESIAN LANGUAGE SUBJECT GRADE 4 - Nur Fa’an Alifatul Maula; Abu Zaeni (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This research was motivated by the initial finding that many students were not yet able to correctly write numbers and represent monetary values. To address this issue, learning was designed using the role-playing method as a pedagogical strategy. The main goal was to improve writing skills in Indonesian language—with a focus on introducing numbers and the concept of monetary value—through the implementation of role-playing in the classroom. The study was conducted using a Classroom Action Research (CAR) approach to gather data on improving learning practices as well as enhancing the quality of teacher and student performance, in terms of professional, knowledge, and skill aspects. The assessment results show that the students' average score in the pre-cycle stage was 58.45; after the Cycle I intervention, it increased to 81.59; and in Cycle II, it reached 89.09. These findings demonstrate that the students' initial ability was below the Minimum Mastery Criteria (KKM), but there was a significant increase in achievement in both action cycles.